Effect of Bailing capsule complicated with low-calcium peritoneal dialysis solution on residual renal function and microinflammatory status in peritoneal dialysis patients with chronic renal failure - Li, Xiancheng; Zhao, Yafeng; Yu, Xiaoyong; Wang, Shufei; Qu, Kai; Wang, Yu (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to ascertain the efficacy of Bailing capsule (BLC) combined with low-calcium peritoneal dialysis solution (PDS) in peritoneal dialysis (PD) patients with chronic renal failure (CRF).MethodsNinety-two patients with CRF were randomly divided into a control group (n = 45) and a study group (n = 47). The control group received low-calcium peritoneal dialysis combined with a low-protein diet and compound α-ketoacid tablets, while the study group received BLC in addition to the control group’s treatment. Outcome measures included clinical efficacy, residual renal function (RRF), microinflammatory status, nutritional status, oxidative stress markers, and the incidence of adverse reactions.ResultsThe study group demonstrated a significantly higher total effective rate compared to the control group (P < 0.05). Post-treatment, the study group exhibited a reduced rate of RRF decline, lower levels of serum tumor necrosis factor-α, C-reactive protein, and interleukin-6, improved serum prealbumin, albumin, transferrin, and hemoglobin levels, reduced serum malondialdehyde levels, and increased serum superoxide dismutase and glutathione peroxidase levels compared to the control group (P < 0.05). There was no significant difference in the overall incidence of adverse reactions between the two groups during treatment (P > 0.05).ConclusionThe combination of BLC with low-calcium PDS is effective in PD patients with CRF, demonstrating the ability to slow the decline of RRF, improve microinflammatory status, enhance nutritional and oxidative stress parameters, and maintain a comparable safety profile without increasing the incidence of adverse reactions.